ANALYSIS OF THE SALES AND INCOMES BETWEEN DIFFERENT CATEGORIES OF AGRICULTURAL PRODUCTS - Vukadinović, Predrag; Damnjanović, Aleksandar; Dimitrijević, Ljiljana (Economics of Agriculture, 2017)
In this paper, dynamic analysis of the sale and income four different categories of agricultural products on the Republic of Serbia was described. Differentiating incomes by sales points, all of mentioned agricultural categories was stratified and observed as two separate time series. A comparative statistical analysis and correlation structure of their dynamics was investigated. For this purpose, various statistical methods, based on the time series analysis, was used. This analysis has been shown a high correlation between the incomes of the same, as well as different categories of agricultural products. Therefore, this study should indicate in which direction and to what sectors of agricultural production should be to move more intensive budgetary support.